Risk factors of depression among adults attending primary care clinics in Kuantan, Pahang, Malaysia - Md Aris, Mohd Aznan (2009)
Depression disorder is one of the common mental health problems that occur in any age with an increasing in trends. The objectives of this study were to determine the prevalence and its associated factors among adult attending primary care clinics in Kuantan, Pahang. A cross sectional study design was carried out. The respondents were selected through convenient sampling from those who attended the primary care clinics in Kuantan, Pahang during the study period. The data was collected using a structured self-administered questionnaire which includes social-demographic background, medical illness, history of substances abuse and depression assessment. The Brief Patient Health Questionnaire (PHQ-9) was used to screen the presence of depression among the respondents. From 1st June to 30rd September 2008 of the study period, 452 respondents agreed to enroll in the study. The respondents comprised of Malay (84.5%), males (54.2%) and married (69.7%) adult. Most of them received secondary education background (56.4%), self-employed/private sector workers (46.9%) with median income per capita of RM 333 per month and non-smoker (76.8%). A few of them were involved in drug abused (0.7%), consumed alcohol (2.4%), suffered from chronic illness (21.7%) and 10.6% had depression (according to PHQ-9). The study revealed that depression were found significantly associated in those with chronic illness {OR: 2.702, 95%CI (1.409, 5.184)}, and involved in drug abused {OR: 39.152, 95%CI (1.662, 992.291)} among the adult respondents. The study concluded that the adult with history of involved in drug abused or suffered from chronic illness require greater attention in health policy of the primary care clinics